2002
DOI: 10.4049/jimmunol.168.6.2782
|View full text |Cite
|
Sign up to set email alerts
|

Complement Receptor Type 1 (CD35) Mediates Inhibitory Signals in Human B Lymphocytes

Abstract: The complement system—particularly component C3—has been demonstrated to be a key link between innate and adaptive immunity. The trimolecular complex of complement receptor type 2 (CR2), CD19, and CD81 is known to promote B cell activation when coligated with the B cell Ag receptor. In the present study, we aimed to elucidate the role of human complement receptor type 1 (CR1), the other C3-receptor on B cells. As ligand, aggregated C3 and aggregated C3(H2O), i.e., multimeric “C3b-like C3”, are used, which bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
75
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 49 publications
3
75
0
Order By: Relevance
“…The human CR1 (CD35) negatively regulates the proliferation and differentiation of activated B cells after binding to its natural ligand: the complement activation fragment C3b [6,7,25]. King-Konert et al reported a fast reduction of the titer of anti-dsDNA autoantibodies in SLE patients treated with the chimeric molecule ETI-104, a construct of dsDNA, coupled covalently to a murine human CR1-specific mAb [26].…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…The human CR1 (CD35) negatively regulates the proliferation and differentiation of activated B cells after binding to its natural ligand: the complement activation fragment C3b [6,7,25]. King-Konert et al reported a fast reduction of the titer of anti-dsDNA autoantibodies in SLE patients treated with the chimeric molecule ETI-104, a construct of dsDNA, coupled covalently to a murine human CR1-specific mAb [26].…”
mentioning
confidence: 99%
“…We constructed several chimeric antibodies by coupling the dsDNA-mimicking peptides or peptides, parts of histone 1 molecule to a rat anti-mouse FcgRIIb-binding mAb. When administrated in lupus-prone MRL/lpr mice they reduced the levels of anti-histone1 and anti-dsDNA IgG antibodies and proteinuria, and prolonged the overall survival [23,24].The human CR1 (CD35) negatively regulates the proliferation and differentiation of activated B cells after binding to its natural ligand: the complement activation fragment C3b [6,7,25]. King-Konert et al reported a fast reduction of the titer of anti-dsDNA autoantibodies in SLE patients treated with the chimeric molecule ETI-104, a construct of dsDNA, coupled covalently to a murine human CR1-specific mAb [26].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…iC3b can be cleaved again by Factor I to yield C3dg. Human CR1 has also been identiBied as a receptor for MBL, leading to phagocytosis, (Ghiran et al, 2000) and plays an inhibitory role in human adaptive immunity by reducing B lymphocyte proliferation following cross--linking of surface IgM by anti--IgM antibodies (Józsi et al, 2002). In humans, CR1 expressed on erythrocytes has an important function in clearance of immune complexes from blood.…”
Section: Complement Receptorsmentioning
confidence: 99%